From the Editors - Burkiewicz, Łukasz (Perspektywy Kultury, 2021)
The topic of Issue 32 of Perspectives on Culture is Christianity and its role as a source of not only European, but also a geographically wider cultural sphere (e.g., the Egyptian Copts). Three pillars were fundamental to the construction of Europe’s current cultural identity: Athens as a source of philosophy, Rome as the foundations of law, and Jerusalem as a place where religion was born. Christianity created a new cultural heritage upon the achievements of Athens and Rome, having respect for the legacy of the previous civilizations. There is no doubt that Christianity has made an important contribution to European culture. In this issue, an important place is given to the person of Pope John Paul II, whose teachings and thoughts appear in several texts.